RESEARCH AND ORGANIZATIONAL ACTIVITIES OF UNESCO CHAIRS AND UNITWIN NETWORK - Gennadiy A. Bordovskiy; Irena V. Robert; Alexander V. Khoroshilov (Высшее образование в России)
The article presents the model of interaction and the main directions of cooperation between the UNESCO IITE, the Network of UNITWIN/UNESCO Chairs and the Interuniversity network UNITWIN RAO on ICT application in education and innovative pedagogics. The main areas of activities of the participants of the UNESCO global network are education, research, and innovationin thesphere of integration of ICT and pedagogy. The general scheme of interaction of the UNESCO IITE and participants of the Network assumes establishment of basic platforms or the coordination centers providing the corresponding researches and implementation of practical tasks.